2017
DOI: 10.1371/journal.pone.0173364
|View full text |Cite
|
Sign up to set email alerts
|

The incidences and risk factors related to early dysphagia after anterior cervical spine surgery: A prospective study

Abstract: Dysphagia is a common complication following anterior cervical spine surgery (ACSS). The incidences of dysphagia were variable and controversial. The purpose of this study was to determine the incidence of early dysphagia after ACSS with a new scoring system, and to identify the risk factors of it. A prospective study was carried out and patients who underwent ACSS from March 2014 to August 2014 in our hospital were included in this study. A self-designed dysphagia questionnaire was delivered to all of the pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 19 publications
2
27
0
Order By: Relevance
“…In a retrospective multicenter study of 2,827 ACDFs, Wang et al [ 30 ] also found that patients who developed immediate postoperative dysphagia had a higher BMI than those who did not (27.3 vs. 24.6 kg/m 2 , p ≤ 0.001). Liu et al [ 27 ] reported a similar result during the first to second postoperative days. Our results agree with these studies, that obesity is associated with early postoperative dysphagia.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…In a retrospective multicenter study of 2,827 ACDFs, Wang et al [ 30 ] also found that patients who developed immediate postoperative dysphagia had a higher BMI than those who did not (27.3 vs. 24.6 kg/m 2 , p ≤ 0.001). Liu et al [ 27 ] reported a similar result during the first to second postoperative days. Our results agree with these studies, that obesity is associated with early postoperative dysphagia.…”
Section: Discussionmentioning
confidence: 56%
“…Incidence rates of dysphagia after ACDF vary in the literature from 1 to 79% [29][30][31] . A large database study with 2,723 patients conducted by Chung et al reported an incidence of 2.3%, with patients over 70 years old having higher risk 32 .…”
Section: Dysphagiamentioning
confidence: 99%
See 1 more Smart Citation
“…The authors have suggested the association between obesity and early-dysphagia may be linked to the increased thickness of the prevertebral tissue in obese patients, leading to difficulty in manipulation and excessive esophageal retraction. 26,30,31 Finally, while no past study has elucidated the implication of frailty in the development of dysphagia, the present publication demonstrated a significant association. Frailty which is defined as hypoalbuminemia, muscle weakness or fatigue may make patients especially susceptible to more intraoperative tissue manipulation and thus at increased risk of postoperative dysphagia.…”
Section: Patient Related Risk Factorsmentioning
confidence: 40%
“…In contrast to some studies regarding obesity [ 6 , 27 , 29 ], our results showed that body mass index was significantly associated with dysphagia. Similarly, Wang et al [ 26 ] and Liu et al [ 30 ] found increased rates in the immediate postoperative period only. The authors have suggested the association between obesity and early-dysphagia may be linked to the increased thickness of the prevertebral tissue in obese patients, leading to difficulty in manipulation and excessive esophageal retraction [ 26 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 86%